Pemahaman Guru TK Tentang konten Pembelajaran SAINS AUD Di Kecamatan Padang Panjang Barat Kota Padang Panjang - Dewi, Ayu Citra (Kiddie: Early Childhood Education and Care Journal, 2023)
The purpose of this research is to describe the level of understanding of kindergarten teachers in the city of Padang Panjang about the concept of science learning for early childhood. This research uses a quantitative approach with a descriptive survey method, namely a questionnaire. The population in this study were kindergarten teachers in the city of Padang Panjang west, totaling fifty four kindergarten teachers. Determination of the sample using nonprobability sampling with saturated sampling technique, namely the entire population is used as a sample. The collected data were grouped into five categorization groups, namely very good, good, poor, very poor and then analyzed using statistical analysis with the average formula. The results showed that the level of understanding of kindergarten teachers in the city of Padang Panjang about science learning content for early childhood was good, namely 67.8. Suggestions for kindergarten teachers in research are that it is hoped that teachers can add insight into science concepts for early childhood even better